High resolved snow height measurements at Neumayer Station, Antarctica, 2024 - Schmithüsen, Holger; Conrat, Pablo (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2025)
At Neumayer-Station in Antarctica snow height is permanently monitored with a laser distance meter. The instrument measures continuously since 2013-01-01 and is located in the vicinity of the Air Chemical Observatory Neumayer. By design, the sample area of the surface is on the order of a few millimetre in diameter. Long-term trends of the measured snow height are strongly correlated with accumulation on the ice shelf at a horizontal scale of several kilometres. Short-term trends reflect dynamic changes of the surface and can be used to deduce information on surface roughness.